2007
DOI: 10.1111/j.1551-2916.2007.01957.x
|View full text |Cite
|
Sign up to set email alerts
|

Ceramics with Special Porous Structures Fabricated by Freeze‐Gelcasting: Using tert‐Butyl Alcohol as a Template

Abstract: By a novel freeze-gelcasting technique, ceramic bodies with unidirectional ordered and gradient porous structures were fabricated, using tert-butyl alcohol (TBA)/acrylamide (AM)/ alumina (Al 2 O 3 ) slurries. TBA, which can freeze below 251C and volatilize rapidly above 301C, was used as a template for forming pores. The porous structures could be controlled by the temperature conditions, resulting in special unidirectional and gradient porous structures over a long range of several millimeters. At the same ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
111
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(114 citation statements)
references
References 14 publications
1
111
0
2
Order By: Relevance
“…During cooling, the dispersant freezes and thus segregates from the particle-rich domains 166 and acts as a macroporogen, which is finally removed by sublimation. Next to aqueous suspensions, freeze casting based on organic dispersants, such as tert-butylalcohol, [167][168][169] camphene 170 or 1,4-dioxane 171 has been reported in the literature. The pores generated by the freeze casting technique are usually in the range of 1 mm up to several hundreds of micrometres.…”
Section: Zeolitic Monoliths Via Freeze Castingmentioning
confidence: 99%
See 1 more Smart Citation
“…During cooling, the dispersant freezes and thus segregates from the particle-rich domains 166 and acts as a macroporogen, which is finally removed by sublimation. Next to aqueous suspensions, freeze casting based on organic dispersants, such as tert-butylalcohol, [167][168][169] camphene 170 or 1,4-dioxane 171 has been reported in the literature. The pores generated by the freeze casting technique are usually in the range of 1 mm up to several hundreds of micrometres.…”
Section: Zeolitic Monoliths Via Freeze Castingmentioning
confidence: 99%
“…169 Subsequently, the obtained 'green body' has to be consolidated via a final solidification step (e.g. via sintering 167 ). For materials which are not able to solidify themselves, binders are usually added to the initial suspension, which are then responsible for the durable solidification (see also Section 4.1).…”
Section: Zeolitic Monoliths Via Freeze Castingmentioning
confidence: 99%
“…This is why all classes of materials and composites made from them can, in principle, be prepared by freezing polymer solutions, metal or ceramic particle suspensions or novel micro-and nanocomposites consisting of polymer, ceramic or metal fibres and particles in a polymer solution. While the majority of freeze-cast materials is still prepared using aqueous solutions or slurries, other liquid vehicles, such as camphene (Sofie & Dogan 2001;Araki & Halloran 2005;Shanti et al 2006;Lee et al 2007a,b;Yoon et al 2007;Yook et al 2008Yook et al , 2009), camphene-naphthalene (Araki & Halloran 2004a) and tert-butyl alcohol (Chen et al 2007), are also increasingly being used. Important in the choice of the liquid carrier are properties such as its crystal structure and type of growth during solidification and its interaction with the solids dissolved or suspended in it.…”
Section: Processing Biomaterials By Freeze Castingmentioning
confidence: 99%
“…A consequence of this may be that the properties of unidirectional porous ceramics are anisotropic. Chen et al [80] reported that the compressive strengths in the axial and radial directions of unidirectional porous alumina fabricated by the freeze casting method were 153 ± 30 and 54 ± 14 MPa, respectively, confirming the presence of a high degree of anisotropy in the strength of this unidirectional porous microstructure. Figure 5 compares the bending strength as a function of porosity of unidirectional porous alumina prepared by the extrusion method using fibers (EF) [71] with porous alumina prepared by conventional sintering [71,81], hot pressing (HP) [82], hot isostatic pressing (HIP) [81] and pulsed electric current sintering (PECS) [82].…”
Section: Mechanical Propertiesmentioning
confidence: 85%